Unified Energy Agents as a Base for the Systematic Development of Future Energy Grids - Derksen, Christian; Linnenberg, Tobias; Unland, Rainer; Fay, Alexander (11th German Conference Proceedings, 2013)
The need for the application of software agents and agent-technologies in highly diversified future energy grids is widely accepted today. Nevertheless, the very general concept of the agent paradigm still leads to misunderstandings and to the fact that agents are meant and utilized for very different tasks. Accordingly, the approaches that were presented in the Smart Gird area have major weaknesses in terms of comparability and a subsequently large-scale use. We claim that the introduction of a unified definition of an Energy Agent will help to create a coherent picture that can accelerate further discussions and the conversion of the energy supply. Considering a development cycle that consists of modeling and implementation, simulation, test-bed application and the deployment to real systems, we present here our definition of an Energy Agent that takes into account the law of conservation of energy. Further, we present a classification of Energy Agents according to their sophistication and integration level and outline the need for individual but standardized energetic option models.